The Influence of Sit-Up Exercise on Backstroke Swimming Skills in Physical Education Students - Muhammad Farhan; Muh. Mawardi; La Robi (Journal Of Sport Education (JOPE), 2025)
Backstroke swimming is a sport that requires body coordination, core muscle strength, and efficient breathing and movement techniques. Abdominal muscle strength plays a crucial role in maintaining body stability on the water surface and improving movement efficiency. Sit-ups, a form of abdominal muscle strengthening, are thought to positively impact backstroke performance. This literature review aims to analyze previous research on the relationship between sit-up training and improved backstroke performance. The literature reviewed was sourced from national and international journals in the fields of sports and physiology. The results indicate that programmed sit-ups can increase abdominal muscle strength, improve posture, and enhance arm and leg propulsion efficiency. Integrating sit-ups with core exercises such as planks, leg raises, and dynamic movements yields optimal benefits. However, further experimental research is needed to measure the direct impact on speed, energy efficiency, and body stability in the water. This review provides a theoretical basis for coaches to design more effective backstroke training programmed.